Competitive advantage of customer centricity - Parniangtong, Sathit Jack, 1953- (Springer, 2017)
This book presents strategies that put the customer at the center of an enterprise. It elaborates on the reasons for viewing customers as assets that a firm needs to acquire, develop and cultivate in order to generate profitable relationships, and champions customer profitability as the metric for measuring business performance. Further, it advocates the need to provide solutions to customers' requirements with bundles of products and services. It broadens the definition of customer value beyond tangible benefits and price to include both tangible and intangible benefits and total ownership costs, while embracing a variety of unique customer needs. The book highlights the value of business planning, marketing and sales mechanisms and changing employee behavior to create lifelong, high-value profitable customer relationships that satisfy the customer's needs. Competitive Advantage of Customer Centricity maps a new journey that entire organizations must undertake in order to achieve these lucrative goals.
Keywords: Marketing research.; Customer relations -- Management.; elektronické knihy; electronic books